Effect of Probiotic Fermented Cabbage Waste on Broiler Chicken Performance to Increase Production - Ikhwana, Abdi; Elfawati, Elfawati; Saleh, Eniza; Jati, Putri Zulia; Zaki, M (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Cabbage waste fermented liquid (Brassica oleracea) is a type of fermented liquid that contains lots of vitamins and other important nutrients that are beneficial for broilers. This study aims to determine the effect of adding fermented cabbage waste to the percentage of weight and length of the digestive organs of broilers including the weight of the proventriculus and ventriculus. This research was carried out from March to May 2021 at the Laboratory of UIN Agriculture Research and Development Station (UARDS) Faculty of Agriculture and Animal Husbandry, Sultan Syarif Kasim State Islamic University, Riau. The research material used 80 DOC broilers (CP 707). The research method was an experiment using a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments consisted of P0 (control drinking water), P1 (2 ml of fermented cabbage waste/liter of drinking water), P2 (3 ml of fermented cabbage waste/liter of drinking water), and P3 (4 ml of fermented cabbage waste/liter of water). drinking water). The parameters measured were the percentage of weight of the proventriculus and ventriculus. The results of the analysis of variance showed that the administration of fermented cabbage waste in drinking water to broilers did not have a significant effect (P>0.05) on the percentage of weight and length of the digestive organs of broilers. The conclusion of this study is that the administration of fermented cabbage waste liquid to a level of 4 ml/liter of drinking water in broilers has not been able to increase the weight and length of the digestive organs of broilers